The Long-Horn Beetles (Family: Cerambycidae) in the Muhammad Sabki City Forest Area, Jambi City - Sakinah, Audriella Nadine; Wulandari, Tia; Putra, Dhean Primanda; Suhanda, Robet (Jurnal Biologi Tropis, 2024)
Muhammad Sabki City Forest Park (THKMS) is generally used as an educational tourism area. Organisms that have not been identified in the THKMS area include longhorn beetles (Cerambycidae). Longhorn beetles (Cerambycidae) are a type of insect that in its larval phase lives on rotting wood that will dry out. Longhorn beetles (Cerambycidae) are spread across several primary and secondary forests, to degraded forests, so that Cerambycidae can be used as environmental bioindicators. Collection of longhorn beetle samples (Cerambycidae) was carried out using purposive random sampling. Sampling was carried out in two utilization zones in the THKMS area, namely the moderate utilization zone and the low utilization zone. Longhorn beetle samples (Cerambycidae) were taken using the jackfruit branch trap method (Artocarpus trap) with 10 Artocarpus traps installed in each zone, and the determination of the trap location was carried out randomly. The result shows there are several species of longhorn beetles that are only found at certain stations. There are 8 species of longhorn beetles that can be found at both stations. The species that are only found at station 1 (low utilization zone) are 1 (Sybra sp.) and the species that are only found at station 2 (moderate utilization zone) are 3 species (Acalolepta rusticatrix, Acalolepta sp. and Pterolophia sp.3). Each genus has its own characteristics of morphology so that it can be distinguished based on morphological characters.